2000
DOI: 10.1046/j.1365-2036.2000.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and gastric cancer − the clinicians' point of view

Abstract: Although the incidence of gastric cancer has declined dramatically in Western countries, the most recent data from the International Agency for Research on Cancer show that it remains the second most common cancer worldwide and caused 628 000 deaths in 1990. The incidence and prevalence of gastric cancer are projected to increase over the next few decades in less developed countries as a result of the increased longevity of H. pylori-infected populations and improved therapies. Gastric carcinogenesis is a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 65 publications
0
31
0
4
Order By: Relevance
“…10,11 Similarly, other studies have established a strong relationship between H. pylori infection and gastric adenocarcinoma, although the nature of the relationship is still controversial. [12][13][14][15] Moreover, there is a strong association between H. pylori infection and low-grade gastric lymphoma arising from mucosa-associated lymphoid tissue. 16 H. pylori infection also has been associated with dyspepsia and non-ulcer dyspepsia, although this association is still unresolved.…”
Section: Association Between H Pylori Infection and Diseasementioning
confidence: 99%
“…10,11 Similarly, other studies have established a strong relationship between H. pylori infection and gastric adenocarcinoma, although the nature of the relationship is still controversial. [12][13][14][15] Moreover, there is a strong association between H. pylori infection and low-grade gastric lymphoma arising from mucosa-associated lymphoid tissue. 16 H. pylori infection also has been associated with dyspepsia and non-ulcer dyspepsia, although this association is still unresolved.…”
Section: Association Between H Pylori Infection and Diseasementioning
confidence: 99%
“…Helicobacter pylori (H pylori) is a microaerophilic, Gramnegative bacterium, and is implicated often as the causative agent of chronic gastritis, duodenal and gastric ulcers, and gastric carcinoma [1,2] . H pylori-associated disorders usually regress or heal completely after treatment with antibiotics [3] .…”
Section: Introductionmentioning
confidence: 99%
“…The PAI encodes a bacterial type IV secretory system that secretes and translocates the cagA protein into host cells, where it is phosphorylated by a host-cell kinase and causes morphological changes. Innocenti et al, found that several, but not all, H pylori strains are able to activate endothelial cells to express the adhesion molecules VCAM-1, ICAM-1, and E-selectin and to secrete neutrophil-recruiting chemokines, and therefore contribute to tissue damage and ulcer formation [48,49] . Among people infected with H pylori, the virulence of the infecting strain is a major determinant which develops disease.…”
Section: H Pylorimentioning
confidence: 99%